Deformation and Velocity Wave Propagation in a Thin Isotropic Plate - Klimenda, Frantisek; Skocilasova, Blanka; Skocilas, Jan; Soukup, Josef (Manufacturing Technology Journal, 2024)
The propagation and velocity of the deformation wave in the thin isotropic plate is investigated. The deformation is induced by the stroke of impact body onto the facial surface of the plate. The plate is supported perpendicularly. The excitation of the plate oscillation is initialized by a unit force (Heavi-side's jump). The impact body has a rounded facet by radius c = 2.5 mm. Hook's material model and Kirchhoff's and Fluegge's geometric model have been investigated. The analytical solutions for both models are presented. The MATLAB script has been assembled to solve material and geometrical mod-els. The results were compared for two selected points on the surface of the plate. Plate deformation was recorded at two points T1 (at a distance of 20 mm from the impact location on the x axis) and T2 (at a distance of 20 mm from the impact location on the y axis).
Keywords: Thin supported isotropic plate; Impact loading; Hooke's material model; Kirchhoff's and Fluegge's geometrical model